Common injuries area among archers - Mohd. Hashim, Asha Hasnimy; Kamal, Talib; Halijah, Ibrahim; Zainal Abidin, Zainuddin (2008)
The definition of injury is the key to understanding and comparing data regarding injury incidence. Injury definitions range from any complaint voiced by an athlete to any medical event severe enough to require physician evaluation or to limit participation in sports. Archery is a sport with a low reported incidence of associated injury. It can be expected that injury does occur because of the repetitive nature of the action of drawing a bow. Archers do not appear to recognize chronic aches and pains as being due to injury. Therefore the purposes of this study are to identify and analyze the common injuries area among archers related to overuse or damage of muscle and tendons of the upper limb relating to shoulder, elbow, wrist and finger joints. The survey has been conducted to thirty subjects that were randomly chosen from one national competition. The data then been analyzed using Statistical Packages for Social Science version 14.0 (SPSS 14.0). The results show that the most frequently injured area is at finger joints (41.5%) followed by shoulder (40.2%), elbow (15.8%) and wrist (2.5%). It is suggested; in order to avoid overuse injuries due to nature of sports coaches and archers should be aware of the risk of injury and should advise training.